Signature of click chemistry in exosome modification for cancer therapeutic - Nobendu Mukerjee; Swarup Sonar (Wiley, 2024)
Abstract Exosomes, small extracellular vesicles secreted by cells, have gained attention as potential therapeutic agents due to their natural ability to deliver biomolecules and traverse biological barriers. However, their limited targeting specificity and payload capacity necessitate modifications for improved therapeutic efficacy. Click chemistry, known for its high specificity, efficiency, and mild reaction conditions, offers an innovative solution for modifying exosomal surfaces. This technique enables precise attachment of targeting ligands, imaging agents, and therapeutic molecules, enhancing the targeting, delivery, and overall effectiveness of exosome‐based therapies. By addressing cancer heterogeneity, click chemistry‐modified exosomes can target diverse cancer cell populations within tumors, improving treatment specificity and reducing drug resistance. The development of copper‐free click chemistry, such as strain‐promoted azide‐alkyne cycloaddition (SPAAC), minimizes toxicity, ensuring biocompatibility and safety. As research progresses, this approach holds great promise for personalized and effective cancer treatment, paving the way for next‐generation therapeutics and diagnostics.